EFEKTIVITAS LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS LINGKUNGAN DITINJAU DARI HASIL BELAJAR IPS SISWA SMP YAKHALUSTI PONTIANAK - Rika Anggela; Rina Rina (STKIP Singkawang, 2023)
The aim is to objectively and systematically determine the effectiveness of environmentally based student worksheets (LKPD) in terms of social studies learning outcomes for Yakhalusti Middle School students. This research used Quasy experimental design with a two group posttest only design. The population in this research were students from Yakhalusti Pontianak Middle School with the research sample determined using Cluster Random Sampling, namely class VII A with 25 students and VIIB with 25 students. Data collection techniques use observation, tests and documentation. The data analysis technique uses T-Te Pair Samples by fulfilling the prerequisite tests, namely Normality and Homogeneity Tests. Based on the results of the research and discussion, it can be concluded that: 1) The learning outcomes of the control class obtained an average score of 68 which is within the sufficient criteria; 2) the learning outcomes of experimental class students using environment-based LKPD obtained an average score of 77 which is within the Good criteria. 3) the t table value, then compare it with the calculated t value (7.320 > 2.073). Because the calculated t value is greater than the t table, it can be concluded that H0 is rejected and Ha is accepted. This means that there is an average difference between the learning outcomes of the control class and the experimental class, which means that there is also the effectiveness of environmentally based LKPD on students' social studies learning outcomes.